2006
DOI: 10.1111/j.1748-1090.2006.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors that affect maternal behaviour and breeding success in great apes in captivity

Abstract: In this paper the relationship between maternal behaviour and breeding success (or failure) in great apes is described. Data were gathered from a questionnaire survey returned by 48 zoos and from available studbook data, giving a total sample size of 687 individuals [Gorillas Gorilla gorilla (n= 277), Bonobos Pan paniscus (n= 37), Chimpanzees Pan troglodytes (n= 216) and Orangutans Pongo pygmaeus (n= 157)] born between 1990 and 2000 at 86 institutions. The factors influencing maternal behaviour are discussed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
(67 reference statements)
0
18
0
Order By: Relevance
“…High infant mortality rates have been reported in zoo orangutan populations, possibly as a result of rearing by humans. Abello and Colell (2006) reported that zoo orangutans reared by humans had more offspring dying \1 year after birth than those reared by their biological mothers. Cocks (2007) also reported that in zoos, female orangutans reared by humans rejected their infants at higher rates than biological mother-reared females.…”
Section: Factors Influencing Higher Infant Mortality Ratementioning
confidence: 98%
“…High infant mortality rates have been reported in zoo orangutan populations, possibly as a result of rearing by humans. Abello and Colell (2006) reported that zoo orangutans reared by humans had more offspring dying \1 year after birth than those reared by their biological mothers. Cocks (2007) also reported that in zoos, female orangutans reared by humans rejected their infants at higher rates than biological mother-reared females.…”
Section: Factors Influencing Higher Infant Mortality Ratementioning
confidence: 98%
“…However, the opportunity to observe breeding during development appeared to be the most significant condition, favouring breeding in hand‐reared ♀♀ reaching adulthood. As already statistically demonstrated in a previous study related to maternal behaviour, the opportunity to observe social behaviours within conspecifics could increase the likelihood that Gorillas will demonstrate a good repertoire of natural social behaviours as adults (Abelló & Colell, 2005). The breeding probability is three times more likely for hand‐reared ♀♀ that observe breeding behaviour than for those that did not, reinforcing the results reported by Meder (1989).…”
Section: Discussionmentioning
confidence: 88%
“…The remaining 255 births were born to 111 mother‐reared ♀♀, 60 hand‐reared ♀♀ and 84 wild‐caught ♀♀, with 83 deaths reported. For further information, see Abelló & Colell (2006a,b).…”
Section: Discussionmentioning
confidence: 99%